SIFAT FISIK KAYU LAPIS BERBAHAN BAKU KAYU AKASIA (Acacia mangium Willd) DAN KELAMPAYAN (Anthocephalu spp) - Arsad, Effendi (Kementerian Perindustrian, 2011)
The utilization of acacia and kelampayan wood as plywood materials were done. There are two kinds of treatments with two cores samples. Wood core with thickness 2 mm and 3 mm with the spreading rate of adhesive 150 gr/m2, 200 gr/m2 and 250 gr/m2. Resuls showed that the water content of plywood are 9,01% - 14,29% for acacia and 9,17% - 10,58% for kelampayan wood material. The density of the plywood are 0,62 gr/cm3 – 0,73 gr/cm3 for acacia and 0,44 gr/cm3 – 0,57 gr/cm3. for kelampayan wood material. The tensile strength of plywood are tensile strength of plywood are 9,49 kg/cm2 – 14,73 kg/cm2 for acacia and 8,61 kg/cm2 – 12,58 kg/cm2 for kelampayan wood material.Keywords: acacia, kelampayan, the spreading rate of adhesive, physics characteristic, plywood